2015
DOI: 10.1210/jc.2014-3887
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency, An Independent Risk Factor for Isolated Hypothyroxinemia in Pregnant and Nonpregnant Women of Childbearing Age in China

Abstract: An association between ID and isolated hypothyroxinemia was found in both pregnant and nonpregnant childbearing-aged women, independent of the effects of iodine and thyroid autoimmunity. We speculate that ID may be a pathogenic factor for hypothyroxinemia, even in pregnant women during the first trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 36 publications
(41 reference statements)
5
54
0
3
Order By: Relevance
“…In the present study, serum FT4 concentrations were lower and TSH concentrations were higher in subjects with iron deficiency, in line with previous studies (10,20,26) and the difference between the IDA group and MID was significant. TT4 levels were not significantly different among different groups, which may be relevant to the specific status during early pregnancy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, serum FT4 concentrations were lower and TSH concentrations were higher in subjects with iron deficiency, in line with previous studies (10,20,26) and the difference between the IDA group and MID was significant. TT4 levels were not significantly different among different groups, which may be relevant to the specific status during early pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…In a study of Swiss pregnant women in the second and third trimester, Zimmermann et al (9) reported that poor maternal iron status predicts both higher TSH (thyroid stimulating hormone) and lower TT4 (total thyroxine) concentrations. Yu et al (10) reported that serum FT4 (free thyroxine) levels were significantly lower in pregnant women with ID (iron deficiency) compared with the corresponding groups without ID. However, the number of related studies remains very small, especially for subjects in the first trimester.…”
mentioning
confidence: 99%
“…Previous studies did not take TAI into account, or used it as an exclusion criterion to investigate the relationship between ferritin and thyroid function (11,12). The importance of our results lays in the fact that the presence of TAI has been associated in both spontaneous and assisted pregnancies with impaired outcomes, including (recurrent) miscarriage, preterm delivery, low birth weight and postpartum thyroiditis (15,16).…”
Section: Discussionmentioning
confidence: 91%
“…The prevalence we observed was in line with that in most other studies, although in a recent Chinese study, a lower prevalence of ID (<10%) was noticed. This discrepancy may be explained by different socioeconomical states (most of our patients are non-employed), by the fact that we excluded patients taking iron supplements at the time of ferritin measurement and finally because we measured ferritin levels later in pregnancy as compared with the Chinese study, in which it was measured before the 12th week of pregnancy (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation